Association of overt hypothyroidism with risks of cognitive impairment: a meta-analysis and systematic review - Zhu, Jinxin; Xu, Jialu; Li, Zhaoqing; Liu, Jia (Frontiers in Endocrinology, 2025)
BackgroundStudies examining the relationship between overt hypothyroidism (oHT) and the risk of cognitive impairment (CI) have yielded mixed results. This study aimed to evaluate the association between oHT and the risk of CI.MethodsWe systematically searched relevant studies published up to March 2025. Data were extracted independently by two investigators. Overall odds ratios (ORs) and their 95% confidence intervals (CIs) were calculated using a random-effects model. The Newcastle-Ottawa Scale (NOS) was used to assess the quality of cohort and case-control studies, while the Agency for Healthcare Research and Quality (AHRQ) scale was used for cross-sectional studies. Results were reported following PRISMA guidelines.ResultsA total of 11 studies involving 1,190,059 participants were included in the systematic review. Meta-analysis revealed that oHT was associated with an increased risk of CI (OR = 1.18, 95%CI=1.04–1.34). When CI was categorized into mild cognitive impairment (MCI) and severe cognitive impairment (Alzheimer’s disease (AD) or all-cause dementia), oHT was associated with an increased risk of MCI (OR = 1.24, 95%CI=1.13–1.36) but not with AD (OR = 1.03, 95%CI=0.77–1.38) or all-cause dementia (OR = 1.20, 95%CI=0.94–1.53). Subgroup analysis based on diagnostic methods for oHT showed that oHT diagnosed solely by TSH levels was associated with a reduced risk of CI (OR = 0.87, 95%CI=0.79–0.95).ConclusionAvailable evidence suggests an association between oHT and an increased risk of cognitive impairment, particularly MCI. However, given the observational nature and significant heterogeneity of this study, the strength of this association still requires high-quality prospective studies for final confirmation and precise quantification.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251012792.